Capturing the political? The role of political analysis in the multi-disciplining of development studies. - Hickey, S (GPRG, 2005)
This article analyses the recent resurgence of political analysis within international development. It argues that although new conceptual approaches have brought valuable insights concerning the links between popular agency, institutional politics and development possibilities, several problems remain. These include a tendency either to overlook or to under-theorise some important linkages between politics and development; a general reluctance to engage critically with the notion of development itself or to disaggregate key concepts such as ‘poverty’; a reluctance to adopt insights from political economy perspectives, and a problematic tendency towards quantifying political phenomena. Overall, the contribution of political analysis to a genuinely multidisciplinary development studies turns on its capacity to reveal how ‘the political’ as well as ‘politics’ links to development, a task achieved most successfully in approaches that weave historical and political sociology perspectives into political analysis, and engage with critical theory.